2008
DOI: 10.1017/s0967199408004668
|View full text |Cite
|
Sign up to set email alerts
|

In vitroageing of pig oocytes: effects of the histone deacetylase inhibitor trichostatin A

Abstract: After in vitro maturation, the unfertilized pig oocytes underwent the process called ageing. This process involves typical events such as fragmentation, spontaneous parthenogenetic activation or lysis. Inhibition of histone deacetylase, using its specific inhibitor trichostatin A (TSA), significantly delayed the maturation of pig oocytes cultured in vitro. The ageing of oocytes matured under the effect of TSA is the same as the ageing in oocytes matured without TSA. The inhibition of histone deacetylase during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…To delay or even prevent the ageing process in oocytes stored in vitro, treating them with some chemicals and antioxidant agents, such as caffeine in pigs (Kikuchi et al 2002), nitric oxide (Goud et al, 2005 a, b) and DL-dithiothreitol in mice (Rausell et al, 2007) and humans (Tarin et al, 1998) and trichostatine A in pig (Jeseta et al, 2008) and mice (Huang et al, 2007) has been proposed and applied. In addition, melatonin has been reported to reduce oxidative stress in aged mouse oocytes and to delay the onset of apoptosis, which is the end point of the oocyte ageing process .…”
mentioning
confidence: 99%
“…To delay or even prevent the ageing process in oocytes stored in vitro, treating them with some chemicals and antioxidant agents, such as caffeine in pigs (Kikuchi et al 2002), nitric oxide (Goud et al, 2005 a, b) and DL-dithiothreitol in mice (Rausell et al, 2007) and humans (Tarin et al, 1998) and trichostatine A in pig (Jeseta et al, 2008) and mice (Huang et al, 2007) has been proposed and applied. In addition, melatonin has been reported to reduce oxidative stress in aged mouse oocytes and to delay the onset of apoptosis, which is the end point of the oocyte ageing process .…”
mentioning
confidence: 99%
“…In addition, it was recently shown that it inhibits histone deacetylase (HDAC; Marks and Breslow 2007). Moreover, Jeseta et al (2008) showed that HDAC inhibition delays spontaneous aging in pig oocytes. In the present study, mouse oocytes were treated with HDAC inhibitors such as trichostatin A and sodium butyrate to determine whether the effects of DMSO are linked to HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Akiyama et al (2006) demonstrated that manipulation of histone acetylation in maturing oocytes induces aneuploidy and has a detrimental effect on subsequent embryonic development. On the other hand, TSA is able to enhance the viability of oocytes matured to metaphase II that were not fertilized and underwent a spontaneous detrimental process designated as aging (Jeseta et al, 2008). Also, Rybouchkin et al (2006) described the positive effects of histone deacetylase inhibition on the development of embryos that had been created using somatic cell nuclear transfer.…”
Section: Discussionmentioning
confidence: 99%